Implikasi Pendidikan Karakter dalam Novel Lelaki Pembawa Kain Kafan Karya Griven H. Putera - Septiana, Vonica; Shomary, Sudirman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
Character education plays an integral part in shaping human personality and behavior, with its values often found in literary works. Literature serves not only as a form of entertainment but also as a platform for conveying deep moral and ethical values. This research examines the values of character education in the novel "Lelaki Pembawa Kain Kafan" by Griven H. Putera. The focus on this novel is chosen due to the diverse range of character values it presents, such as religiosity, respect, compassion, responsibility, and discipline. Qualitative methods are employed in this study, involving steps such as defining the research project, formulating research questions, collecting data through observation and analysis, and an iterative process to draw conclusions. Descriptive methods are also used to depict the phenomena of character values in the novel. Data is drawn from the novel "Lelaki Pembawa Kain Kafan" published by the Department of Culture & Tourism of Riau Province, focusing on five main character values: trustworthiness, respect, responsibility, justice, and compassion. The research findings indicate that this novel reflects a variety of character education values through characters such as Pak Jupen, Pak Guru, Nantan, Pudin, Bahri, Ncik Soma, Pak Imam, and Pak Wali. The dominant character value is religiousness, as evidenced by the attitudes exhibited by the main characters, particularly Pak Jupen. In conclusion, this novel illustrates the importance of character values in shaping human personality and behavior, especially within the context of traditional society.